Analysis of Tensile Strength’s Influence on Limit Height and Active Earth Pressure of Slope Based on Ultimate Strain Method - Jianping Xin; Yingren Zheng; Yingxiang Wu; Abi Erdi (Advances in Materials Science and Engineering)
In the geotechnical engineering, the tensile failure of soil is disregarded for a long time. Actually, the tensile strength of soil is very low and the tensile failure really occurs, especially in the slope engineering. The limit height and active earth pressure of slope will change when considering the effect of tensile failure. In this paper, we try to figure out the limit height and active earth pressure of slope by using the new numerical limit analysis method, the ultimate strain method. The results, without considering tensile failure and with considering tensile failure, are compared with the analytical solutions. It is proved that the ultimate strain method is credible and feasible in the slope engineering. The result shows that the tensile strength has a great influence on the limit height of the unsupported slope, but little influence on supported slope. It also has obvious influence on the active earth pressure of supported slope when the value of tensile strength is small, and the smaller the tensile strength the larger the influence. But the earth pressure becomes stable when the value of tensile strength is over 10 kN, and it is much close to the one calculated without considering the tensile failure.